Los recursos electrónicos de información en humanidades en las páginas web de las universidades norteamericanas. - Gracia Armendáriz, Juan (Revista General de Información y Documentación, 2000)
A selection of compilations of resources in the Humanities available on North American Universities web page is presented, analysed and assessed. Selection has been made of a sample of universities maintaining information resources on the Internet and also those proyecta, catalogues, data bases or in formation instruments specialising in the Hurnanities (Art, Philosophy, Litera ture and History) created by the afore-mentioned institutions.
Keywords: Information resources; Internet; Humanities; North American unuver sities